The Use of Guessing Games to Teach Speaking Skill - Yuyun Maqfirah (Universitas Syiah Kuala, 2018)
Speaking skill is a priority in learning English. However, it is perceived as the most complicated skill since it happens in real time situation. Many students were unable to speak English well because they get bored in learning process which leads to inability in mastering the materials taught by teachers, especially in speaking skill that requires students to participate enthusiastically. As the solution, teachers can use Guessing Game (GG) which is able to motivate the learners to speak. This research aimed to investigate the implementation of GG in improving the fluency aspect in speaking skill of Class VIII students at SMP Inshafuddin Banda Aceh. Pre-experimental with one-group pretest-posttest design was applied. The data were collected by conducting pretest and posttest. The population was second grade students of SMP Inshafuddin Banda Aceh and the sample was Class VIII B chosen through random sampling technique. The data were analyzed using t-test formula. The result revealed that tscore (4.2) is higher than ttable 2.093 (tscore ttable). It means Ho is rejected and Ha is accepted. Thus, GG improves students’ fluency in speaking skill in Class VIII B of SMP Inshafuddin Banda Aceh. Teachers are suggested to apply GG in teaching speaking skill.